Impact of strategic orientation on sustainable competitive advantage: the mediating role of organizational capabilities - Mohammed Majeed; Ahmed Tijani; Kwame Simpe Ofori; Aidatu Abubakari; George Oppong Appiagyei Ampong (Cogent Social Sciences)
Emerging economies face numerous challenges; thus, gaining and sustaining competitive advantage has become imperative. Despite the relevance of competitive advantage, its linkages with organizational capabilities and strategic orientation remain underexplored. Thus, this study examines the determinants of firms’ sustainable competitive advantage. Specifically, it analyzes the impact of strategic orientation on organizational capabilities, and how social media capability mediates the relationship between strategic orientation and sustainable competitive advantage. The study employed a quantitative research approach, and the sample consisted of 305 non-traditional exporters from Ghana, who were purposively sampled from the Ghana Export Promotion Authority database. The proposed model was tested using the partial least squares approach to structural equation modelling (PLS-SEM) on SmartPLS 3. The study revealed that strategic orientation has a significant positive effect on technology, social media, and marketing capabilities. In addition, a significant positive relationship was found between social media capabilities and technological capabilities, as well as between marketing capabilities and firm competitive advantage. This finding suggests that social media and technological and marketing capabilities aid firms in realising the full potential of their strategic orientations, which in turn influences sustainable competitive advantage.